Correlation of Anti-Müllerian Hormone Level with Ki-67 Expression in Patients with Ovarian Cancer - Annisa Waskito (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: This research was carried out to discover the correlation between the AMH serum in patients with malignant ovarian tumor of epithelial type with the Ki-67 expression as a marker of proliferation, therefore it was expected through the research to know the role of AMH in the inhibition of proliferation and growth of malignant ovarian tumor of epithelial type. Method: The study design was cross-sectional, with data obtained retrospectively from 24 medical records of patients with malignant ovarian of epithelial type, who had been examined for AMH levels in 2009, along with the sample in the form of preparation of paraffin embedded tissue of malignant ovarian tumor patients, who fulfilled the inclusion criteria. Furthermore examination of Ki-67 expression was performed with the statistical analysis using the rank Spearman analysis. Result: There was a negative correlation between AMH levels and Ki-67 expression in patients with malignant ovarian tumors of epithelial (r = -0.652, p < 0.05). Conclusion: These data indicate a significant negative correlation between serum AMH levels and Ki-67 expression in epithelial ovarian cancer patients. [Indones J Obstet Gynecol 2011; 35-2: 87-90] Keywords: anti-müllerian hormone, epithelial ovarian cancer, Ki-67, Müllerian inhibiting substance